EFEKTIVITAS PUDING JAMBU BIJI MERAH TERHADAP PENURUNAN TEKANAN DARAH PADA PREHIPERTENSI DI PUSKESMAS PADASUKA KOTA BANDUNG: EFFECTIVENESS OF RED GUAVA PUDDING TOWARDS REDUCING BLOOD PRESSURE IN PREHYPERTENSION AT PADASUKA PUBLIC HEALTH CENTER OF BANDUNG - Yuswandi, Sheninna Chandika Galuh; Pusparini, Pusparini; Mulyo, Gurid Pramintarto Eko; Isdiany, Nitta (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
Prehypertension is an early condition that can cause arterial hypertension in its later development into cardiovascular disease. Low intake of vitamin C and high intake of sodium at productive age have the risk of triggering the development of degenerative diseases such as hypertension. This study aims to determine the effectiveness of giving guava pudding on blood pressure in the prehypertension group in the work area of ​​the Padasuka Public Health Center, Bandung City. This type of research is a quasi two group with a control experimental design using pre-test and post-test. The sampling technique used is simple random sampling. Intake data were collected using a Semiquantitative Food Frequency Questionnaire (SFFQ) method while blood pressure data was measured using a Digital Sphygmomanometer. The research data were analyzed using Paired T-Test and Wilcoxon test. The results showed that the average intake of vitamin C in the treatment group increased by 186% and sodium intake decreased by 19.1%, better than the control group, the decrease in systolic blood pressure in the treatment group was 3.2% or higher than the control group and an average The treatment group's diastolic blood pressure decreased 5.2% or lower than the control group. There was an effect of the intervention on the intake of vitamin c and sodium in the treatment group (p<0.05). There was an effect on vitamin c intake (p<0.05) and no effect on sodium intake in the control group (p>0.05). The results of the study on systolic blood pressure in the treatment group showed an effect of giving the intervention product (p<0.05) while the diastolic blood pressure in the treatment group, systolic blood pressure, and diastolic blood pressure in the control group showed no effect on giving the intervention product (p>0.05). The study concluded that there was an effect of giving red guava pudding on systolic blood pressure, but there was no difference in the decrease in systolic and diastolic blood pressure between the two sample groups.